HIV-1 induces NALP3-inflammasome expression and interleukin-1β secretion in dendritic cells from healthy individuals but not from HIV-positive patients. - Pontillo, Alessandra; Silva, Lais T; Oshiro, Telma M; Finazzo, Claudia; Crovella, Sergio; Duarte, Alberto J S (AIDS, 2012)
OBJECTIVE: NALP3-inflammasome is an innate mechanism, alternative to type-1 interferon, which is able to recognize nucleic acids and viruses in the cytoplasm and to induce pro-inflammatory response. Here, we hypothesized the involvement of inflammasome in the early defense against HIV-1 and in the full maturation of dendritic cells: for this, we evaluated the response of dendritic cells pulsed with HIV-1 in terms of inflammasome activation in healthy donors. Moreover, inflammasome response to HIV was evaluated in HIV-infected individuals. DESIGN AND METHODS: Monocyte-derived dendritic cells isolated from 20 healthy individuals (HC-DC) and 20 HIV-1-infected patients (HIV-DC) were pulsed with alditrithiol-2-inactivated HIV-1. We then analyzed inflammasome genes expression and interleukin-1β (IL-1β) secretion. RESULTS: In HC-DC, HIV-1 induced higher NLRP3/NALP3 mRNA expression compared with other inflammasome genes such as NALP1/NLRP1 or IPAF/NLRC4 (P < 0.001). This augmented expression was accompanied by CASP1-increased and IL1B-increased mRNA levels and by a significant increment of IL-1β secretion (P < 0.05). Otherwise, HIV-1 failed to activate inflammasome and cytokine production in HIV-DC. HIV-DC showed an increased NLRP3/NALP3 basal expression, suggesting a chronic inflammatory profile of patients' immune cells. CONCLUSION: HIV-1 was able to induce a NALP3-inflammasome response in healthy individuals, indicating that this inflammasome could play a role in the first steps of HIV-1 infection; the consequent inflammatory process may be important for directing host immune response against the virus and/or disease progression. HIV-DC seemed to be chronically activated, but unresponsive against pathogens. Our findings could be of interest considering the ongoing research about dendritic cell manipulation and therapeutic strategies for AIDS involving dendritic cell-based immune-vaccines.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Brazil; Carrier Proteins; Caspase 1; Cells, Cultured; Dendritic Cells; DNA, Viral; Female; HIV-1; Humans; Immunity, Innate; Inflammasomes; Interleukin-1beta; Male; Tumor Necrosis Factor-alpha